Observation of factors associated with visceral swallowing pattern in 2-6 year old children: A cross-sectional study - Babak Sayahpour; Magda-Anastasia M; Nicolas Plein; Stefan Kopp; Sara Eslami; Sarah Bühling (Elsevier, 2024)
Introduction: The association between the visceral swallowing pattern (VSP) and dentofacial abnormalities remains controversial. This cross-sectional study aimed to investigate the association between the VSP and various factors including type of birth, gender, tongue posture, lip incompetence, eruption of primary molars, habits and the presence of malocclusions in children with primary and early mixed dentition. Material and method: A total of 219 children (102 boys and 117 girls) were evaluated using a combination of a questionnaire and a structured clinical examination by one pediatric specialist dentist. Kittel's method of tongue posture evaluation and the Payne technique for assessment of swallowing pattern were included in the clinical examination of myofunctional status. After checking for normality, normal and non-normal distributed data were analyzed using two-sample t-test and Mann-Whitney U test, respectively. Analysis of categorical variables was done using a chi-square test, and Bonferroni correction was used as correction for multiple comparisons. Results: A total of 56.2 % of the study population had a VSP. The chi-square test indicated a statistically significant higher presence of VSP in male gender. Statistically significant associations were seen between the VSP and lip incompetency, pathologic resting tongue position, habits, anterior open bite and increased overjet. On the other hand, no statistically significant associations were found between VSP and children's age within the sample population, type of birth, uni- or bilateral crossbites, increased overbite, edge-to-edge anterior bite or completion of eruption of primary molars and/or permanent incisors. Conclusions: The association between VSP and male gender, pathologic tongue posture, lip incompetency and habits and occlusal traits such as anterior open bite and increased anterior overjet is supported by the results of the present study.